Insurance from responsibility in light of the Iraqi Doctors Protection Law No. 26 of 2013. - Younes Hussein, Assistant Lecturer: Faten (The college of law and political science journal, 2023)
doctors the obligating of importance the on affirmed legislations Most professional his cover to ,professions other like just ,policy insurance by the against insurance an have to and ,others toward responsibility civil due or mistake medical to due ,patients to happen could that damage the ,happened that of any if so ,results required the achieving not to pay to ,contract the to according ,obligated be will company insurance the to paid was that fees the fits that ,patients the to compensation a paying to contribute will industry medical the in insurance the ,so ,doctor insurance the ,company insurance the by compensation the of some.